Literackie obrazy odpowiedzialności człowieka w edukacji najmłodszych = Literary images of responsibility in the education of youngest generation - Waloszek, Danuta (Zielona Góra: Uniwersytet Zielonogórski)
With important lifestyle information, literary is one of the channels in reaching the childrenmind. There have been lot of battles about fairy tales, and their sense about approaching world of values to a child. One side of battle always consider a fairy tale as a something bad, interrupting child's development, others think that it's something good, which could evolve point of distinguishing good and evil, stupiclity and knowledge and as a point of building responsibility, as well as for others and themselve
Keywords: dydaktyka literatury; edukacja; dziecko